2018
DOI: 10.1017/s1368980018001246
|View full text |Cite
|
Sign up to set email alerts
|

Examining associations between school food environment characteristics and sugar-sweetened beverage consumption among Canadian secondary-school students in the COMPASS study

Abstract: We identified that the school food environment characteristics examined here had little impact on adolescents' days of SSB consumption. While schools should adopt or maintain a comprehensive policy approach to discourage students' SSB intake, population-level interventions focusing on other contexts (e.g. home and community) are needed to complement existing school-based interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 55 publications
3
28
1
Order By: Relevance
“…party, holidays). Previous studies had already identified the availability of SSB at home (28,48,(57)(58)(59) and school (60) ; having parents (48,58,59,61) and friends (58,62) who consume SSB; the taste of SSB (54) and eating at fast-food restaurants (58) as correlates of SSB consumption among adolescents. The two facilitating factors were an easy access to water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…party, holidays). Previous studies had already identified the availability of SSB at home (28,48,(57)(58)(59) and school (60) ; having parents (48,58,59,61) and friends (58,62) who consume SSB; the taste of SSB (54) and eating at fast-food restaurants (58) as correlates of SSB consumption among adolescents. The two facilitating factors were an easy access to water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important that population-level interventions are implemented together with school-based interventions, as recommended by Godin et al . ( 10 ) in this issue.…”
mentioning
confidence: 89%
“…Five articles (9)(10)(11)(12)(13) in this issue of Public Health Nutrition highlight a range of issues related to the food environment and educational settings, and it is worthwhile to consider how the results of the different studies could contribute to the ongoing discourse about the food environment in and around schools and how individuals act in and interact with this environment.…”
mentioning
confidence: 99%
See 2 more Smart Citations